2014
DOI: 10.5543/tkda.2014.24892
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac tamponade as the first clinical sign of gastric adenocarcinoma: a rare condition

Abstract: Cardiac tamponade originating from a primary gastric cancer (GC) is a rare condition. Patients are generally asymptomatic until the disease is advanced. We report a rare patient with cardiac tamponade as the first manifestation of primary GC. A 46-year-old male was admitted with progressive dyspnea. Cardiac tamponade was diagnosed on two-dimensional ultrasonographic echocardiography. Pericardiocentesis yielded 1500 ml of bloody fluid. Pericardial cytologic examination was positive for malignant cells. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
0
4
0
4
Order By: Relevance
“…Pour malignant pericardial is a complication that can be related to neoplastic disease on which, if not diagnosed and quickly conducted it can be potentially deadly [6]. The breast carcinoma, melanoma and lymphoma tumors are the most related to pericardial metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Pour malignant pericardial is a complication that can be related to neoplastic disease on which, if not diagnosed and quickly conducted it can be potentially deadly [6]. The breast carcinoma, melanoma and lymphoma tumors are the most related to pericardial metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Based on an analysis of 17 cases of gastric cancer-induced neoplastic cardiac tamponade, Kobayashi et al suggested that systematic chemotherapy may facilitate long-term survival, although they did not observe any statistically significant differences in survival [6]. For gastric cancer-induced carcinomatous pericarditis, the following systematic chemotherapies have been reported to be useful in previous case reports and case series: S-1, S-1 + cisplatin, oxaliplatin + 5-fluorouracil + leucovorin, S-1 + Irinotecan, and docetaxel [6][7][8][9][10][11]. Nonetheless, complete cure is difficult [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…For gastric cancer-induced carcinomatous pericarditis, the following systematic chemotherapies have been reported to be useful in previous case reports and case series: S-1, S-1 + cisplatin, oxaliplatin + 5-fluorouracil + leucovorin, S-1 + Irinotecan, and docetaxel [6][7][8][9][10][11]. Nonetheless, complete cure is difficult [6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Під час аналізу виявлено 3 повідомлення про клінічний прояв РШ у вигляді ТС. УП внаслідок шлункової патології зустрічається вкрай рідко, і більшість повідомлень стосуються шлунково-перикардіальних фістул (ШПФ) [4,20]. У всьому світі опубліковано лише близько 65 повідомлень про ШПФ [4].…”
Section: результатиunclassified